ELOS-based path following control for underactuated surface vehicles with actuator dynamics. (1st September 2019) - Yu, Caoyang; Liu, Chunhu; Lian, Lian; Xiang, Xianbo; Zeng, Zheng
Abstract: This paper presents an improved extended state observer-based line-of-sight (ELOS) guidance law for robust path following of underactuated surface vehicles without linear velocity measurement. First, two extended state observers are resorted to separately estimate the surge and sway linear velocities, such that the unmeasured side-slip angle can be indirectly calculated and accurately compensated in the line-of-sight guidance law. Especially, in this improved ELOS design no assumptions on constant or small side-slip angle are made. Second, a more high-order sliding mode surface is defined for the input of third-order heading tracking subsystem due to actuator dynamics. Subsequently, an adaptive fuzzy sliding mode control (AFSMC)-based tracking law is designed to robustly track the heading guidance angle without a prior on the vehicle's complex hydrodynamics parameters. Finally, comparative simulation results are provided to show the performance of the designed path following controller, composed of ELOS and AFSMC for underactuated surface vehicles with actuator dynamics. Highlights: An improved ELOS guidance law accurately estimates time-varying side-slip angle. A model-free AFSMC law is designed for robust tracking with actuator dynamics. Comparative examples validate adaptive and robust performance of the controller.